Tanggung Jawab Debitur Terhadap Objek Jaminan Fidusia Dalam Perjanjian Kredit Kendaraan: (Studi Di PT. FIF Group Mataram) - I Nyoman Yudi Mahendra; Mohammad Irfan (Fakultas Hukum Universitas Mataram, 2022)
This study aims to find out how to settle credit, if an event occurs where the object of the guarantee is lost at the time of the agreement or the installment period has not been completed in the vehicle loan agreement and to find out the responsibility of the creditor for the object that is guaranteed to be lost during the installment has not been completed. This type of research is empirical normative legal research. The method used in this research is a statutory approach, conceptual and sociological approach. The results of the study reveal that the responsibility of the debtor can be accounted for by the creditor by providing relevant evidence and the settlement process can be through the courts but to make it easier and faster it is chosen through negotiations or by deliberation.